Is information part of on-farm equipment? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
workshop on agricultural information in Central Africa. The meeting was organized by CTA in Libreville, Gabon (October 7-11, 1991)